Cervical Cancer Risk and Screening Among Women Seeking Assistance With Basic Needs. Issue 8 (August 2021) - Kuroki, Lindsay M.; Massad, L. Stewart; Woolfolk, Candice; Thompson, Tess; McQueen, Amy; Kreuter, Matthew W.
Abstract : (Abstracted from Am J Obstet Gynecol 2021;224(4):368.e1–368.e8) In the United States, more than 50% of cervical cancers occur in inadequately screened patients. Social and structural determinants of health contribute to inadequate screening rates.